The newspaper K'inhyegaman bayrakh (the flag of labour) for displaced persons: typological features (Herald of Journalism, 2022)
Based on new sources, which have become available, some aspects of ideological work among the Chechens and Ingush deported to Central Asia and Kazakhstan in 1944 are examined. The purpose of the study is to identify the specifics of the Chechen-language newspaper Qinhyegaman Bayrakh (The Flag of Labour), published in Almaty in 1955-1957 for Chechen special resettlers. The author emphasised its role in ethnic preservation and the development of the Chechen and Ingush languages/literature. In particular, an attempt is made to explain the reason why the mass media silenced the large-scale campaign to liquidate the autonomous republic and the forcible relocation of the entire ethnos to Central Asia and Kazakhstan. This aspect of Stalin's deportations has yet to be explained in the scientific literature. Therefore, revealing the motives behind the Bolshevik regime's genocide against the peoples is still relevant. The study is based on the methodology of analysis of historical phenomena, using methods of literary criticism. The article uses materials from the personal archive of a former employee of the editorial board, S.D. Magomayev. For the first time in historical journalism, the object of study is a publication targeted deported people. It characterizes the typological features of a publication for internally displaced persons, which appeared against the background of the unmasking of Stalin's personality cult. For example, the very topic of deportation was banned from the pages of a publication intended for its victims. The analysis undertaken reinforces the thesis that genocide against individuals, social groups and even peoples is a characteristic feature of any totalitarianism. The results of the study are of value to historians of national journalism; they will also allow forming an objective picture of the crime that brought entire ethnic groups to the brink of total extinction.Keywords: deportation of peoples in the USSR,Chechens and Ingush,special resettlement newspaper, K'inkhyegaman bairakh (The Flag of Labour).